Transcription Expression and Clinical Significance of Dishevelled-3 mRNA and δ-Catenin mRNA in Pleural Effusions from Patients with Lung Cancer. (23rd February 2012) - Li, Xiao-Yan; Liu, Shu-Li; Cha, Na; Zhao, Yu-Jie; Wang, Shao-Cheng; Li, Wei-Nan; Wang, En-Hua; Wu, Guang-Ping
Abstract : Objective . To evaluate diagnostic utility of Dishevelled-3 (DVL-3) mRNA and δ -catenin mRNA expression in pleural effusions of patients with lung cancer. Methods . DVL-3 mRNA and δ -catenin mRNA levels were assessed by performing RT-PCR on pleural effusion specimens from patients with lung cancer (n = 75 ) and with lung benign disease (n = 51 ). Results . The expressions of DVL-3 mRNA and δ -catenin mRNA were significantly higher in malignant than in benign lung disease (P < 0.01 ) and were obviously higher than cytology in adenocarcinoma (P < 0.01 ). In single use, DVL-3 mRNA had the highest specificity (94.1%) and PPV (95.7%), whereas δ -catenin mRNA had the highest sensitivity (92.0%) and NPV (88.5%). When combinations of markers were evaluated together, DVL-3 mRNA and δ -catenin mRNA gave a high-diagnostic performance: sensitivity of 100.0%, NPV of 100.0%, and accuracy of 96.0%, respectively. Conclusion . As molecular markers of detecting pleural micrometastasis, DVL-3 mRNA and δ -catenin mRNA are helpful to diagnose the cancer cells in pleural effusions of patients with lung cancer.